Web 2.0 Tools in Documentation and Information Center: Knowledge Management Model - Paletta, Dr., Francisco Carlos; Ayres, Carla; Morais, Thais Fernandes; Zanchet, Gisele (Cadernos de Educação Tecnologia e Sociedade, 2022)
This paper aims to examine concepts of Web 2.0, knowledge management, information management, enterprise portals, Information and Documentation Centre, Virtual Library, and social networking. The methodology used is the systemic literature review. Briefly it narrates the emergency of KM tools and features to its deployment. Relates how knowledge management can help institutions and enterprises in terms of organizing their information and its importance in decision taking. It describes the advancement of Web 2.0 and the ease it brings to society. As results it presents that there are no more borders between people, that everyone can share, discuss, and generate knowledge through the tools that innovative technologies offer.